Sublethal Stress of Pyrethroids on Biochemical Contents in Prostate Gland of a Freshwater Snail, Bellamya bengalensis - A.B. Kulkarni2, D.V. Ahirrao1* and (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Effect of sub lethal concentration of pyrethroid pesticides Fenvulrate (Milfen) and Cypermethrin (Cyperkil) on prostate gland of aquatic snail, Bellamya bengalensis was evaluated. The histological, histochemical and biochemical analysis for 15 days exposed snail was made in the present work. 24 hrs treatment of both pesticides caused cellular swelling. 7 days treatment caused distinct alterations in size, displacement of secretary cells and their arrangement in the globules. 15 days treatment resulted in damage to the prostatic acini and its tubules as well as its cells. The amount of biochemical components was greatly influenced by fenvulrate which causes depletion in glycogen, protein level, whereas cypermethrin stimulated slightly decline in metabolic contents. The ascorbic acid level decreased insignificantly in exposure to both pesticides.